2001
DOI: 10.1002/1521-3773(20010618)40:12<2271::aid-anie2271>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Active Site Design in a Chemzyme: Development of a Highly Asymmetric and Remarkably Temperature-Independent Catalyst for the Imino Aldol Reaction

Abstract: Unusually robust: A remarkably temperature‐independent catalyst has been developed for the imino aldol reaction of imines derived from ortho‐aminophenols (see scheme). This catalyst is prepared from two equivalents of the VAPOL ligand and a zirconium tetraalkoxide. From a consideration of likely intermediates in the catalytic cycle it was deduced that a methyl substituent ortho to the phenol (R1) should enhance induction. This resulted in asymmetric inductions in excess of 98 % ee at room temperature as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 106 publications
(37 citation statements)
references
References 32 publications
0
37
0
Order By: Relevance
“…It was observed that, there was a profound change in asymmetric inductions (>98% ee), when the ortho-position was methylated. 12 The VAPOL-zirconium catalyst is remarkably temperature independent giving an induction of >98% ee at 25 • C and at 100 • C. Moreover, the inductions could be maintained when 2 mol % of the catalyst was employed at 100 • C (Table 3, entries 6-10) and this is true for a variety of imines. Chiral β-amino esters can be then obtained from the corresponding imino-aldol products by treatment with five equiv of cerric ammonium nitrate in 1 M nitric acid (eqs 11 and 12).…”
Section: 9mentioning
confidence: 92%
See 1 more Smart Citation
“…It was observed that, there was a profound change in asymmetric inductions (>98% ee), when the ortho-position was methylated. 12 The VAPOL-zirconium catalyst is remarkably temperature independent giving an induction of >98% ee at 25 • C and at 100 • C. Moreover, the inductions could be maintained when 2 mol % of the catalyst was employed at 100 • C (Table 3, entries 6-10) and this is true for a variety of imines. Chiral β-amino esters can be then obtained from the corresponding imino-aldol products by treatment with five equiv of cerric ammonium nitrate in 1 M nitric acid (eqs 11 and 12).…”
Section: 9mentioning
confidence: 92%
“…The use of VAPOL as a chiral ligand was investigated and was compared with 6,6 -dibromoBINOL and BINOL based catalysts on the imino-aldol reaction mediated by zirconium (eq 10). 12 The catalyst is prepared by reaction of the ligand with 0.5 equiv of zirconium tetralkoxide in the presence of 0.6 equiv of N-methyl imidazole at room temperature for 1 h. It was found that VAPOL and 6,6-diboromoBINOL catalysts are superior to BINOL at −45 • C. 15 When the reaction was performed at room temperature, the asymmetric induction for VAPOL remained unchanged, while that for dibromoBINOL and BINOL decreased. Additionally, a series of imines 19 were prepared where the position of the methyl group on the arene ring was changed.…”
Section: 9mentioning
confidence: 99%
“…[30][31][32][33][34] (3) A biaryl derived catalyst, used in the synthesis of chiral b-amino esters. 35,36 ( …”
Section: Methods Numbermentioning
confidence: 99%
“…20 (2), the resulting Lewis acid (3) catalyzes the addition of silyl ketene acetals to imines in high yield and enantiomeric excess (eqs 7 and 8). 21 In these reactions, the role of N-methylimidazole cannot be overlooked. Isolation of the catalyst prepared from Zr(O-i-Pr) 4 , N-methylimidazole and (R)-6,6 -dibromo-1,1 -bi-2-naphthol revealed that 2 equiv of N-methylimidazole are included in the complex.…”
Section: Diketopiperazine Synthesismentioning
confidence: 99%
“…22 These results are supported by NMR data of catalyst 3 in solution. 21 In a similar fashion, enantioselective addition of Et 2 Zn to imines was accomplished using Zr(O-i-Pr) 4 and peptide-based ligand, 4. 23 This reaction was successfully converted into a three-component, one-pot procedure, allowing imine formation to occur in situ followed by asymmetric addition of Et 2 Zn (eq 9).…”
Section: Diketopiperazine Synthesismentioning
confidence: 99%